2012
DOI: 10.4049/jimmunol.1101116
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Functional P-Selectin Glycoprotein Ligand 1 on Hematopoietic Progenitors Is Developmentally Regulated

Abstract: T cell development requires periodic importation of hematopoietic progenitors into the thymus. The receptor-ligand pair P-selectin and P-selectin glycoprotein ligand 1 (PSGL-1) are critically involved in this process. In this study we examined the expression of functional PSGL-1 on BM hematopoietic progenitors. We demonstrate that functional PSGL-1 is expressed at low levels on hematopoietic stem cells, but upregulated on the cell surface of progenitors that bear other homing molecules known to be important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…This inference was directly confirmed by flow cytometric detection of E-selectin and P-selectin ligands on HPCs and LT-HSCs. These results are consistent with a recent report that also found P-selectin ligands expressed at a low level on HSC [28], and with the BMT data presented above showing that survival of single selectin KO mice is equivalent to that of WT following lethal irradiation and BMT. That report also showed an increase in P-selectin ligands with differentiation, consistent with our finding that LSK cells express higher levels of both E- and P-selectin ligands.…”
Section: Discussionsupporting
confidence: 93%
“…This inference was directly confirmed by flow cytometric detection of E-selectin and P-selectin ligands on HPCs and LT-HSCs. These results are consistent with a recent report that also found P-selectin ligands expressed at a low level on HSC [28], and with the BMT data presented above showing that survival of single selectin KO mice is equivalent to that of WT following lethal irradiation and BMT. That report also showed an increase in P-selectin ligands with differentiation, consistent with our finding that LSK cells express higher levels of both E- and P-selectin ligands.…”
Section: Discussionsupporting
confidence: 93%
“…These demonstrated abilities of LMPPs and CLPs align with the expression of CCR9 and CCR7 by these progenitor populations 52 and also with their expression of functional PSGL-1. 19 After BMT, homing of progenitors to the thymus was greatly reduced. Progenitors trafficking from the blood to the thymus are thought to use mechanisms analogous to those used by mature lymphocytes to enter lymph nodes in which selectin-mediated rolling is followed by chemokine signals activating integrins on the surface of trafficking cells.…”
Section: Discussionmentioning
confidence: 99%
“…30,36 Only LMPPs and CLPs were each able to home to the thymus within 22 hours (Figure 1C), consistent with the known expression of CCR7, CCR9, and functional PSGL-1 on these progenitors, but not upstream HSCs and MPPs. 12,13,19 To estimate the number of progenitors entering the thymus, we performed a short-term homing assay in which sorted cells were plated on OP9-DL4 at limiting dilution. We found that approximately 7 and 30 progenitors homed to the thymus from 1 3 10 7 and 4 3 10 7 BM cells, respectively (supplemental Figure 1 available on the Blood Web site).…”
Section: Lmpps and Clps Each Settle The Normal Thymusmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise identity of the progenitors that migrate to the thymus from circulation remains elusive, it is known that these progenitors require expression of the P-selectin glycoprotein ligand-1 (PSGL-1) and the chemokine receptors CCR7 and CCR9 to gain entry into the thymus (7)(8)(9)(10)(11). Interactions between P-selectin expressed on vascular endothelium and progenitor PSGL-1 are thought to mediate progenitor rolling along endothelial cells in circulation, whereas signaling through CCR7 and CCR9 is thought to be required for integrin activation and subsequent progenitor transmigration through the thymic endothelium, into the thymus (12,13).…”
mentioning
confidence: 99%